EFFECT OF NITROGEN FERTILIZER ON YIELD AND NITROGEN USE EFFICIENCY OF FOUR AROMATIC RICE VARIETIES - Koffi, Djaman; Vincent, Bado B; Valere, Mel C (Emirates Journal of Food and Agriculture, 2017)
The present study aimed to optimize nitrogen fertilizer for higher yield and NUE of modern aromatic rice varieties. Field experiments were conducted at Ndiaye and Fanaye (Senegal) during the dry season and wet season 2012 to evaluate rice response to nitrogen under P and P-K. Five doses of nitrogen (0, 60, 90, 120 and 150 kg /ha) were associated with P (26 kg P /ha); or P-K (26 kg P /ha and 50 kg K /h1). Four aromatic rice varieties Pusa Basmati, Sahel 329, Sahel 177 and Sahel 328 and a non-aromatic variety Sahel 108 were evaluated. Results showed that across genotypes, rice yield varied from 3.3 to 8.6 Mg /ha under N-P fertilizer and from 3.5 to 8.8 Mg /ha under N-P-K fertilizer at Ndiaye. At Fanaye, rice yield varied from 3.7 to 8.6 Mg /ha under N-P fertilizer and from 3 to 10.3 Mg /ha under N-P-K fertilizer. The highest grain yield was obtained by Sahel 177 among the aromatic rice varieties. The optimum nitrogen dose varied with rice genotype and location. The PFPN and the ANUE were influenced by genotype and varied from 161 to 28 kg grain/kg N and from 105.9 to 0.9 kg grain /kg N, respectively. The highest PFPN was obtained by Sahel 108 followed by Sahel 177. K addition to N-P significantly increased ANUE from 6.4 to 20.78 kg grain /kg N. The aromatic rice variety Sahel 177 is the performing alternative to the non-aromatic rice Sahel 108 in the Senegal.